A prospective evaluation of plasma polyphenol levels and colon cancer risk - Murphy, N; Achaintre, D; Zamora-Ros, R; Jenab, M; Boutron-Ruault, M-C; Carbonnel, F; Savoye, I; Kaaks, R; Kühn, T; Boeing, H; Aleksandrova, K; Tjønneland, A; et al. (Wiley, 2018)
Polyphenols have been shown to exert biological activity in experimental models of colon cancer; however, human data linking specific polyphenols to colon cancer is limited. We assessed the relationship between pre-diagnostic plasma polyphenols and colon cancer risk in a case–control study nested within the European Prospective Investigation into Cancer and Nutrition study. Using high pressure liquid chromatography coupled to tandem mass spectrometry, we measured concentrations of 35 polyphenols in plasma from 809 incident colon cancer cases and 809 matched controls. We used multivariable adjusted conditional logistic regression models that included established colon cancer risk factors. The false discovery rate (qvalues) was computed to control for multiple comparisons. All statistical tests were two-sided. After false discovery rate correction and in continuous log2-transformed multivariable models, equol (odds ratio [OR] per log2-value, 0.86, 95% confidence interval [95%CI]=0.79-0.93; qvalue=0.01) and homovanillic acid (OR per log2-value, 1.46, 95%CI=1.16-1.84; qvalue=0.02) were associated with colon cancer risk. Comparing extreme fifths, equol concentrations were inversely associated with colon cancer risk (OR=0.61, 95%CI=0.41-0.91, ptrend=0.003), while homovanillic acid concentrations were positively associated with colon cancer development (OR=1.72, 95%CI=1.17-2.53, ptrend<0.0001). No heterogeneity for these associations was observed by sex and across other colon cancer risk factors. The remaining polyphenols were not associated with colon cancer risk. Higher equol concentrations were associated with lower risk, and higher homovanillic acid concentrations were associated with greater risk, of colon cancer. These findings support a potential role for specific polyphenols in colon tumorigenesis.